Educational activities and the role of the parent in homeschool families with high school students. Issue 3 (2nd July 2016) - Carpenter, Dan; Gann, Courtney
Abstract : Using a qualitative case study approach, this study looked at the educational activities that constitute a typical day in a homeschool family and the role that the parent has within those activities. Three homeschooling families with high school students in a single community in a southern state in the United States participated in the case study. Data was collected using observations, field notes, interviews and artifacts. Analysis of the data pointed to an eclectic mix of instructional modalities and activities used by families. Students often participated in a variety of instructional activities such as online courses, private tutors, and self-taught classes through the use of a flexible daily schedule. Parents were seen to be more of a facilitator or director of educational activities for their children rather than the direct providers of instruction in the homeschool setting.